GP.03 Diagnostic yield of next generation sequencing and myositis autoantibody panels in patients with axial myopathy. (5th June 2019) - Parks, A; Karamchandani, J; Troyanov, Y; Massie, R; O'Ferrall, EK
Abstract : Background: Axial myopathy is a rare neuromuscular disorder of variable etiology characterised by preferential involvement of the paraspinal muscles. We reviewed clinical features of patients with axial myopathies and the diagnostic yield of myositis-associated antibodies and targeted next generation sequencing panels.Methods: We performed a retrospective review of patients presenting with axial myopathy at the Montreal Neurological Hospital from 2011-2018. Data collection included clinical presentation, disease course, results of electromyography, imaging, laboratory and genetic testing, and histopathology on muscle biopsy.Results: Twenty-five patients were identified. Initial manifestation of axial weakness was head drop (15), camptocormia (8), and rigid spine (2). Autoimmune myositis was diagnosed in 9 patients, seropositive in 7 out of 7 tested for myositis-associated antibodies. Genetic testing was consistent with oculopharyngeal muscular dystrophy in one patient and RYR-1 (ryanodine receptor 1) related core myopathy in another. Local radiotherapy or spine surgery preceded the onset of axial weakness in 1 and 6 patients, respectively. Muscle biopsies were available in 17 patients and revealed myopathic changes (16), inflammatory changes (6), and myopathy with vacuoles (3).Conclusions: Recent advancements in genetic and antibody testing, combined with paraspinal muscle biopsy, allow for more precise classification and identification of potentially treatable axial myopathies.